Insights from super-metal-rich stars: Is the Milky Way bar young? - Nepal, Samir; Chiappini, C.; Guiglion, Guillaume; Steinmetz, M.; Pérez-Villegas, A.; Queiroz, A. B.; Miglio, A.; Dohme, P.; Khalatyan, A. (Astronomy and astrophysics, 2024)
Context. Bar formation and merger events can contribute to the rearrangement of stars within the Galaxy in addition to triggering star formation (SF) epochs. Super-metal-rich (SMR) stars found in the solar neighbourhood (SNd) can be used as tracers of such events as they are expected to originate only in the inner Galaxy and to have definitely migrated.Aims. We study a homogeneous and large sample of SMR stars in the SNd to provide tighter constraints on the epoch of the bar formation and its impact on the Milky Way (MW) disc stellar populations.Methods. We investigated a sample of 169 701 main sequence turnoff (MSTO) and subgiant branch (SGB) stars with 6D phase space information and high-quality stellar parameters coming from the hybrid-CNN analysis of the Gaia-DR3 RVS stars. We computed distances and ages using the StarHorse code with a mean precision of 1% and 11%, respectively. Of these stars, 11 848 have metallicity ([Fe/H]) above 0.15 dex.Results. We report a metallicity dependence of spatial distribution of stellar orbits shown by the bimodal distribution in the guiding radius (Rg) at 6.9 and 7.9 kpc, first appearing at [Fe/H] ~ 0.1 dex, becoming very pronounced at higher [Fe/H]. In addition, we observe a trend where the most metal-rich stars, with [Fe/H] ~ 0.4 dex, are predominantly old (9-12 Gyr), but show a gradual decline in [Fe/H] with age, reaching approximately 0.25 dex about 4 Gyr ago, followed by a sharp drop around 3 Gyr ago. Furthermore, our full dataset reveals a clear peak in the age-metallicity relationship during the same period, indicating a SF burst around 3-4 Gyr ago with slightly sub-solar [Fe/H] and enhanced [α/Fe].Conclusions. We show that the SMR stars are good tracers of bar activity.We interpret the steep decrease in the number of SMR stars at around 3 Gyr as the end of the bar formation epoch. In this scenario the peak of bar activity also coincides with a peak in the SF activity in the disc. Although the SF burst around 3 Gyr ago has been reported previously, its origin was unclear. Here we suggest that the SF burst was triggered by the high bar activity, 3-4 Gyr ago. According to these results and interpretation, the MW bar could be young.
Online veröffentlicht: 04. Januar 2024
Gesehen am 06.05.2024